Determinants of Consumer Purchase Intention for Refurbished and Recycled Electronics in the Context of the Circular Economy - Aliya Fahira; Yeshika Alversia (Green Publisher Indonesia, 2025)
The rise in electronic product demand and consumption has led to an increase in electronic waste, posing a challenge to reducing environmental impacts and achieving sustainability. Therefore, transition efforts towards a circular economy, involving various parties including consumers, are needed. This research aims to determine the relationship between factors influencing consumer purchase intentions towards circular economy products, focusing on refurbished electronics and recycled electronics. This research extended the Theory of Planned Behaviour (TPB) by adding environmental concern, perceived risk, and receptivity to green communication variables. Data collection was carried out through questionnaires distributed online using non-probability sampling. Analysis was conducted using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Based on a data sample of 289 respondents, the results show that attitude, subjective norm, perceived behavioural control, and receptivity to green communication variables significantly influence consumer purchase intentions regarding refurbished and recycled gadgets. Another finding is that environmental concern emerges as a positive driver across all TPB factors, while perceived risk negatively impacts consumer attitudes. The research implications suggest that companies should focus on building positive consumer attitudes through quality assurance programs, leverage social influence through environmental campaigns, and develop transparent communication strategies to address perceived risks while highlighting the environmental benefits of circular products.